Dinig sana kita - Sandejas, Mike
The romantic film revolved around a rocker and a deaf boy. One lives in silence while other in noise and fear. The two met in a Baguio camp where hearing kids were mixed with non-hearing kids to find their common ground, which is their love for music--https://en.wikipedia.org/wiki/If_I_Knew_What_You_Said